Arquétipo e representação na telenovela: lugar comum e espaços discursivos na representação do mesmo nas protagonistas - Helena de Manoel Carlos - MIRANDA, Cristia Rodrigues (Universidade Federal do Pará, 2019)
This paper pretends to study some archetypes and models about the compositions in Manoel Carlos’s Helenas-character, considering the cultural industry and mass culture. Therefore, will be used some theses about Morin (1992) about mass culture, and the concept about social representations, the same way that Jodelet (1989) addresses the culture idea and the concept the culture like simulation Subirats (1998). Considering that the mass culture, like simulacrum manifestation about the popular imagination and the ideologies creates social representations and specularly the real is built. Hence, we consider appropriate the regularities and dispersions in the compositions of the Helena-character, because they structured as the logic mass culture and the real reproduction in the form of simulation reproducing and mediating social representations.